Does spacecraft trajectory strongly affect detection of magnetic clouds? - Démoulin, Pascal (2013)
Context. Magnetic clouds (MCs) are a subset of interplanetary coronal mass ejections (ICMEs). One property of MCs is the presence of a magnetic flux rope. Is the difference between ICMEs with and without MCs intrinsic or rather due to an observational bias? Aims. As the spacecraft has no relationship with the MC trajectory, the frequency distribution of MCs versus the spacecraft distance to the MCs’ axis is expected to be approximately flat. However, Lepping & Wu (2010, Ann. Geophys., 28, 1539) confirmed that it is a strongly decreasing function of the estimated impact parameter. Is a flux rope more frequently undetected for larger impact parameter? Methods. In order to answer the questions above, we explore the parameter space of flux rope models, especially the aspect ratio, boundary shape, and current distribution. The proposed models are analyzed as MCs by fitting a circular linear force-free field to the magnetic field computed along simulated crossings. Results. We find that the distribution of the twist within the flux rope and the non-detection due to too low field rotation angle or magnitude only weakly affect the expected frequency distribution of MCs versus impact parameter. However, the estimated impact parameter is increasingly biased to lower values as the flux rope cross section is more elongated orthogonally to the crossing trajectory. The observed distribution of MCs is a natural consequence of a flux rope cross section flattened on average by a factor 2 to 3 depending on the magnetic twist profile. However, the faster MCs at 1 AU, with V > 550 km s-1, present an almost uniform distribution of MCs vs. impact parameter, which is consistent with round-shaped flux ropes, in contrast with the slower ones. Conclusions. We conclude that the sampling of MCs at various distances from the axis does not significantly affect their detection. The large part of ICMEs without MCs could be due to a too strict criteria for MCs or to the fact that these ICMEs are encountered outside their flux rope or near the leg region, or they do not contain a flux rope.